Hip Resurfacing in the Setting of Retained Proximal Femoral Instrumentation or Complex Deformity - Premkumar, Ajay; Ren, Renee; Spaan, Jonathan; Su, Edwin P. (The Journal of Hip Surgery, 2024)
Total hip arthroplasty (THA) in the setting of significant retained femoral instrumentation or complex proximal femoral deformity may be challenging and published reports of THA in this setting reveal sobering results. Hip resurfacing arthroplasty (HRA) is an alternative to THA and may avoid complex hardware removal or deformity correction at the time of hip arthroplasty. Twenty-three patients who underwent elective HRA in the setting of significant proximal femoral deformity and/or retained femoral instrumentation were identified from a prospectively maintained registry. Pre- and postoperative Lower Extremity Assessment Scores (LEAS), modified Harris Hip Scores (mHHS), Hip Disability and Osteoarthritis Outcome Scores for Joint Replacement (HOOS, JR) scores, Visual Analog Scale (VAS) pain levels, and metal ion levels were obtained. Median (interquartile range [IQR]) follow-up was 5.03 (2.07 − 7.91) years, and no patients had undergone revision surgery at their latest follow-up. The mean (standard deviation [SD]) surgical duration was 94.40 (12.00) minutes, and postoperative length of stay was 1.74 (1.80) days. There were no intraoperative complications, and all patients were discharged home. Median (IQR) postoperative LEAS, VAS pain scale, mHHS, and HOOS, JR scores were 13.00 (9.25 − 13.00), 2.50 (0.75 − 10.00), 92.60 (92.40 − 100.00), and 92.34 (85.26 − 100.00), respectively. Fourteen patients completed postoperative serum metal ion level testing at a mean (SD) of 4.24 (2.85) years, where cobalt and chromium levels were 1.22 (0.36) and 2.01 (0.80) parts per billion, respectively. HRA is a viable option for patients with significant proximal femoral deformity or retained instrumentation, and excellent results at mid-term follow-up can be achieved utilizing this strategy in this complex patient population.
Keywords: hip resurfacing arthroplasty; degenerative joint disease; hip arthroplasty; proximal femoral deformity; retained hardware